STRATEGI DIRECT WRITING ACTIVITY SEBAGAI UPAYA PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI BAGI SISWA KELAS II SD - M Habibi; Chandra Chandra (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This research was conducted as the student’s skill in writing descriptive texts in the second grade of SDN 07 Teladan Kota Bukittinggi was still low is because teacher lack an understanding of the step to write a good descriptive. Therefore, this research was intended to describe the improvement of the student’s skill in writing descriptive texts by using Direct Writing Activity strategy in the second grade of SDN 07 Teladan Kota Bukittinggi. This was a classroom action research which used qualitative and quantitative approaches. The subject of research was the practitioner teacher and 32 students in the second grade of SDN 07 Teladan Kota Bukittinggi. The result of the research indicated that the student’s skill in writing descriptive texts improved from 74,48% (adequtae) in the first cycle into 82,94% (good) in the second cycle. It can be concluded, that Direct Writing Activity strategy could improve the student’s skill in writing descriptive text in the second grade of Primary School.Keywords : Writing Skill, Descriptive Texts, Direct Writing Activity strategy